TOF-MS within food and environmental analysis - Rodriguez Fernandez-Alba, Amadeo (Comprehensive analytical chemistry, 2012)
New developments in mass spectrometry have allowed routine identification and lowered limits of detection at levels only imagined a decade ago. Thousands of contaminants and residues in the food supply and the environment are now being reported. Between 2005 and 2010, more than 5,000 publications covering TOF-MS and environmental and food analysis were published, showing the importance of the technique in these applications. This book covers the basic principles of method development in GC- and LC-TOF-MS as well as the main operational parameters related to TOF-MS. The second part focuses on the relevant environmental applications, including quality control aspects as well as data collection. The third part is devoted to relevant applications in food analysis, including validation procedures for screening analysis as well as relevant databases. Outlines basic concepts and principles of gas and liquid chromatography TOF-MS and its application in food analysisIncludes quality control and data collection techniquesFocuses on environmental implications and safety concerns.